Discovering the Site-Selective Umpolung of Ketones Triggered by Hypervalent Fluoro-Iodanes – Why Investigating Side Reactions Matters! - Kretzschmar, Martin; Gulder, Tanja (Synlett, 2023)
In this account, we describe our journey leading to the discovery of a generally applicable umpolung method for the α-functionalization of ketones. Central to this reaction is the cyclic hypervalent fluoro-iodane, which is mostly known for various alkene functionalizations enabling, for example, the synthesis of fluoro-benzoxazepines, indoles, and ketones. During this work, we encountered α-functionalized ketones as minor side products. This observation prompted us to further investigate this reactivity, thus revealing a directed umpolung of pyridyl ketones by the fluoro-iodane. The key to the success was the unexpected non-covalent interaction between the nucleophile, substrate, and iodane.1 Introduction2 Cyclizations Triggered by the Fluorination of Styrenes3 Umpolung Reactions Facilitated by Hypervalent Iodanes4 Discovering and Evolving a Fluoro-Iodane-Triggered Regioselective α-Functionalization of Carbonyl Compounds5 First Investigations on the Nitrogen-Directed Umpolung6 Conclusion
Keywords: hypervalent iodane; fluorination; umpolung of ketones; non-covalent interactions; α-functionalization; halogen bonding